THEORETICAL MODELING OF IMINOISATIN DERIVATIVES AS CORROSION INHIBITORS OF STEEL IN ACID SOLUTION (FUDMA JOURNAL OF SCIENCES, 2020)
The effect of two iminoisatin derivatives [1-morpholinomethyl-3(1-N-dithiooxamide) iminoisatin (molecule 1)] and 1-diphenylaminomethyl-3(1-N-dithiooxamide) iminoisatin (molecule 2) on corrosion inhibition were theoretically investigated using quantum mechanical method. Their electronic parameters and quantum chemical descriptors that predict their adsorption and hence their inhibition efficiency were estimated using the DFT//B3LYP/6-31G (d) method. The results established a relationship between the quantum descriptors and corrosion inhibition efficiency, and also confirmed molecule 2 to be a better corrosion inhibitor and provide a guide to the synthesis of more efficient organic corrosion inhibitors.
Keywords: DFT, Iminosatin, Inhibition efficiency, Quantum descriptors